Pola dan Model Perubahan Pesantren - Mochtar, Affandi (Eduprof : Islamic Education Journal, 2019)
Pesantren are the oldest educational institutions in Indonesia, the bandungan and sorogan systems are classic learning models that were first applied by pesantren before the implementation of madrasi (schools with a tiered system). Historically, Islamic boarding schools have existed in Indonesia for a long time, since they first entered Islam in Indonesia and have become the most important part of the Indonesian nation's struggle against colonialism. In the era of colonialism, pesantren experienced ups and downs in line with the role of the messageren which was considered the power base of the Indonesian nation. However, after the independence of Islamic boarding schools throughout the country, it has grown rapidly, even as an institution it has experienced various innovations that are very encouraging and refreshing the education scene in this country. Pesantren in Indonesia not only preserves its existence as a classic type of education (salaf), but has been biased to adapt and even innovate into a model. and modern educational institutions. Abstrak Pesantren adalah lembaga pendidikan tertua yang ada di Indonesia, sistem bandungan dan sorogan adalah model pembelajaran klasiknyang pertama kali diterapkan oleh pesantren sebelum diterapkannya madrasi (sekolah dengan system berjenjang). Secara histories pesantren telah ada di Indonesia sejka lama, sejak pertama kali masuknua Islam di Indonesia dan menjadi bagain terpenting dari perjuangan bangsa Indonesi dalam melawan kolonialisme. Pada mada kolonialisme pesantren mengalami pasang surut sejalan dengan peran pesanren yang dianggap sebagai basis kekuatan bangsa Indonesia. Namun pasca kemerdekan pesantren di penjuru negri berkembang pesat, bahkan secara kelembagaan mengalami berbagai innovasi yang sangan menggembirakan dan mewarni kancah pendidikan negeri ini.Pesantren di Indonesia tidak saja menjega eksistensinya sebagai pendidikan yang bercorak klasik (salaf), namun telah bias beradaptasi bahkan berinnovasi menjadi model dan lembaga pendidikan modern.